The intellectuals and the peruvian nation. Reflection on the eve of the bicentennial - Gonzales Alvarado, Osmar (2020)
In this article, the author explains how the failure of the Tupacamarista project would open the way for the ideas and actions of the Creoles, and these, through the privileged use of writing, would dominate the world of ideas and, therefore, hence, of ideological projects. Following the route of the transformations of the Creole group, he analyzes its socio-cultural composition and its ideas. The pre-1781 indigenous would no longer have the possibility of resurgence, even when the Creole contingent loses consistency, that is, its capacity as a political subject would no longer be irrelevant. From the middle of the 20th century, the ideological field to be conquered would be disputed by what was left of the small Creole contingent and by the diffuse elements left by the process of postinternal migration cholification and post-Velasquista reforms. Later, Fujimori politics would modify the role of intellectuals. Thus, an unprecedented conflictive process would be configured, of struggle for political, economic, ideological and symbolic power; and for giving meaning to a deeply modified country through new subjects of ideas.